Використання OpenOffice.org Basic для потреб документознавства - Ярка, Уляна; Джигінас, Ольга; Шепелюк, Ольга (Видавництво Львівської політехніки, 2014)
In this article we point out the advantages of using built-in programming language OpenOffice.org Basic. It will save you time and automates frequently used tasks. OpenOffice.org Basic will help you if you are an accountant, economist or even pharmacist.
Keywords: використання ООоBasik у документознавстві; шаблони документів; візуальне програмування